mcr-1-Mediated Colistin Resistance and Genomic Characterization of Antimicrobial Resistance in ESBL-Producing Salmonella Infantis Strains from a Broiler Meat Production Chain in Italy - Patrizia Casagrande Proietti; Laura Musa; Valentina Stefanetti; Massimiliano Orsini; Valeria Toppi; Raffaella Branciari; Francesca Blasi; Chiara Francesca Magistrali; Stefano Capomaccio; Tana Shtylla Kika; Maria Pia Franciosini (MDPI AG, 2022)
This work aimed to evaluate phenotypically and genotypically the colistin susceptibility of 85 Salmonella Infantis strains isolated in Italy from the broiler production chain, and to apply a whole-genome approach for the determination of genes conferring antimicrobial resistance (AMR). All isolates were tested by the broth microdilution method to evaluate the colistin minimum inhibitory concentrations (MICs). A multiplex PCR was performed in all isolates for the screening of mcr-1, mcr-2, mcr-3 mcr-4, mcr-5 genes and whole-genome sequencing (WGS) of six S. Infantis was applied. Three out of 85 (3.5%) S. Infantis strains were colistin resistant (MIC values ranged from 4 to 8 mg/L) and mcr-1 positive. The mcr-1.1 and mcr-1.2 variants located on the IncX4 plasmid were detected in three different colistin-resistant isolates. The two allelic variants showed identical sequences. All six isolates harbored blaCTXM-1, aac(6')-Iaa and gyrA/parC genes, mediating, respectively, beta-lactam, aminoglycoside and quinolone resistance. The pESI-megaplasmid carrying tet(A) (tetracycline resistance), dfrA1, (trimethoprim resistance) sul1, (sulfonamide resistance) and qacE (quaternary ammonium resistance) genes was found in all isolates. To our knowledge, this is the first report of the mcr-1.2 variant described in S. Infantis isolated from broilers chickens. Our results also showed a low prevalence of colistin- resistance, probably due to a reduction in colistin use in poultry. This might suggest an optimization of biosecurity control both on farms and in slaughterhouses.